Epidemiology and Risk Assessment of Pediatric Venous Thromboembolism - Mahajerin, Arash; Croteau, Stacy E. (Frontiers in Pediatrics, 2017)
The incidence of diagnosed venous thromboembolism (VTE) has been increasing concurrent with advances in technology and medical care that enhance our ability to treat pediatric patients with critical illness or complex multi-organ system dysfunction. Although the overall incidence of VTE is estimated at 0.07-0.49 per 10,000 children, higher rates are observed in specific populations including hospitalized children, those with central venous catheters (CVC) or patients convalescing from a major surgery. While the absolute number of pediatric VTE events may seem trivial compared to adults, the increasing incidence, associated with increased mortality and morbidity, the availability of novel therapies, and the impact on the cost of care have made investigation of VTE risk factors and prevention strategies a high priority. Many putative risk factors for pediatric VTE have been reported, primarily from single-institution, retrospective studies which lack appropriate methods for verifying independent risk factors. In addition, some risk factors have inconsistent definitions which vex meta-analyses. CVCs are the most prevalent risk factor but have not consistently been assigned the highest level of risk as defined by odds ratios from retrospective, case-control studies. Few risk-assessment models for hospital-acquired pediatric VTE have been published. Some models focus exclusively on hospitalized pediatric patients while others target specific populations such as patients with cancer or severe trauma. Multi-center, prospective studies are needed to identify and confirm risk factors in order to create a pediatric risk-assessment tool and optimize preventive measures and reduce unintended harm.